Hydrogeology in practice a guide to characterizing ground-water systems - Stone, William J. (William Jay) (Prentice Hall, 1999)
"Understanding ground-water systems and their relationship to the geologic setting is an integral part of characterizing, protecting, and cleaning up the environment. Hydrogeologic studies are the basis for such understanding. This book provides an overview of the basic components and tasks of a sound hydrogeologic study."--BOOK JACKET.